(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The objective of this research was to design a group counselling program based on Cognitive behavioral therapy (CBT), aimed at decreasing the gelotophobia level among male students at Nizwa University. The study sample comprised 36 male students who scored the highest on the gelotophobia scale, and were randomly assigned to either the experimental or control group, each consisting of 18 students. The study sample was randomly divided and distributed into two groups (the experimental group and the control group), so that each of these two groups consisted of (18) participants, where the program (cognitive behavioral therapy) was applied to the experimental group only, which consisted of (6) group counseling sessions. At a rate of two hours per week for 6 consecutive weeks, Results of the study showed significant differences in the gelotophobia scale between the experimental and control groups, with the experimental group showing higher levels of gelotophobia (α ≤ 0.05). The follow-up test conducted one month after the program showed no statistically significant differences between the post-test and follow-up test results of the experimental group, indicating that the program effectively maintained a low level of gelotophobia. Based on these findings, the study concluded that the counseling program was effective in enhancing gelotophobia among male students at Nizwa University.